Hubungan Kualitas Informasi Akun Instagram @museum_geologi dengan Pemenuhan Kebutuhan Informasi Followers - Ayumsari, Ratri; Khadijah, Ute Lies Siti; Saepudin, Encang (Literatify: Trends in Library Developments, 2026)
Phenomenon of content creation has driven the production of more diverse and creative information content. The more information that is produced, the more difficult it becomes for information seekers to sort through and select quality information. The research was conducted to determine the relationship between the quality of information on the Instagram account @museum_geologi and the fulfillment of followers' information needs. The method used was a quantitative research method with a correlational approach. The Instagram followers of @museum_geologi served as the research population with a sample selected using simple random sampling. The sample size was determined based on the Isaac-Michael Table, resulting in 346 sample units. After the data was collected, the data analysis process was conducted through: 1) descriptive statistics analysis and 2) inductive/inferential statistics analysis using IBM SPSS Statistics version 27. The results show that there is a strong and positive relationship between the quality of information on the @museum_geologi Instagram account and the fulfillment of its followers' information needs.